2011
DOI: 10.1093/ndt/gfr321
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium reduces calcification in bovine vascular smooth muscle cells in a dose-dependent manner

Abstract: Background.Vascular calcification (VC), mainly due to elevated phosphate levels, is one major problem in patients suffering from chronic kidney disease. In clinical studies, an inverse relationship between serum magnesium and VC has been reported. However, there is only few information about the influence of magnesium on calcification on a cellular level available. Therefore, we investigated the effect of magnesium on calcification induced by β-glycerophosphate (BGP) in bovine vascular smooth muscle cells (BVS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
108
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(127 citation statements)
references
References 54 publications
(66 reference statements)
12
108
0
7
Order By: Relevance
“…Low serum Mg 2ϩ levels are associated with vascular calcification, and hemodialysis patients with higher serum Mg 2ϩ levels show higher survival (258,259). Although the mechanisms of action are not completely understood, there are two contributing factors: 1) Mg 2ϩ prevents the formation and deposition of Ca/P nanocrystals and the development of appatite structures (83); and 2) Mg 2ϩ inhibits the transdifferentiation of the smooth muscle cells in the vessel well into osteoblast-like cells (282). In both processes Mg 2ϩ prevents vascular calcifiction, and thus hypomagnesemic patients are at risk.…”
Section: Vascular Calcificationmentioning
confidence: 99%
“…Low serum Mg 2ϩ levels are associated with vascular calcification, and hemodialysis patients with higher serum Mg 2ϩ levels show higher survival (258,259). Although the mechanisms of action are not completely understood, there are two contributing factors: 1) Mg 2ϩ prevents the formation and deposition of Ca/P nanocrystals and the development of appatite structures (83); and 2) Mg 2ϩ inhibits the transdifferentiation of the smooth muscle cells in the vessel well into osteoblast-like cells (282). In both processes Mg 2ϩ prevents vascular calcifiction, and thus hypomagnesemic patients are at risk.…”
Section: Vascular Calcificationmentioning
confidence: 99%
“…42 An interesting feature of magnesium is its inhibiting effect on vascular calcifications in in-vitro and experimental models. 43 Some authors observed a significant association between low serum magnesium levels and vascular calcifications in 390 hemodialysis patients. 44 The role of possible magnesium accumulation in bone tissues is still uncertain.…”
mentioning
confidence: 99%
“…In hemodialysis and peritoneal dialysis patients, lower serum magnesium but still within the normal range was associated with an increased severity of vascular calcification [50,51] . In vitro studies have demonstrated the protective effect of increasing magnesium concentration on vascular smooth muscle cell calcification through an upregulation of anti-calcification proteins including matrix gla protein and osteopontin [52][53][54] . The combined magnesium-calcium phosphate binder (calcium acetate 435 mg/magnesium carbonate 235 mg) available in Europe has similar efficacy to sevelamer in reducing serum phosphate and without the side effect of increasing serum ionized calcium.…”
Section: Magnesium and Combined Magnesium-calcium Phosphate Bindermentioning
confidence: 99%